WMJ‐8‐B, a novel hydroxamate derivative, induces MDA‐MB‐231 breast cancer cell death via the SHP‐1‐STAT3‐survivin cascade - Chuang, Yu‐Fan; Huang, Shiu‐Wen; Hsu, Ya‐Fen; Yu, Meng‐Chieh; Ou, George; Huang, Wei‐Jan; Hsu, Ming‐Jen (British journal of pharmacology, 2017)
Background and Purpose Histone deacetylase (HDAC) inhibitors have been demonstrate to have broad‐spectrum anti‐tumour properties and have attracted lots of attention in the field of drug discovery. However, the underlying anti‐tumour mechanisms of HDAC inhibitors remain incompletely understood. In this study, we aimed to characterize the underlying mechanisms through which the novel hydroxamate‐based HDAC inhibitor, WMJ‐8‐B, induces the death of MDA‐MB‐231 breast cancer cells. Experimental Approach Effects of WMJ‐8‐B on cell viability, cell cycle distribution, apoptosis and signalling molecules were analysed by the MTT assay, flowcytometric analysis, immunoblotting, reporter assay, chromatin immunoprecipitation analysis and use of siRNAs. A xenograft model was used to determine anti‐tumour effects of WMJ‐8‐B in vivo. Key Results WMJ‐8‐B induced survivin reduction, G2/M cell cycle arrest and apoptosis in MDA‐MB‐231 cells. STAT3 phosphorylation, transactivity and its binding to the survivin promoter region were reduced in WMJ‐8‐B‐treated cells. WMJ‐8‐B activated the protein phosphatase SHP‐1 and when SHP‐1 signalling was blocked, the effects of WMJ‐8‐B on STAT3 phosphorylation and survivin levels were abolished. However, WMJ‐8‐B increased the transcription factor Sp1 binding to the p21 promoter region and enhanced p21 levels. Moreover, WMJ‐8‐B induced α‐tubulin acetylation and disrupted microtubule assembly. Inhibition of HDACs was shown to contribute to WMJ‐8‐B′s actions. Furthermore, WMJ‐8‐B suppressed the growth of MDA‐MB‐231 xenografts in mammary fat pads in vivo. Conclusions and Implications The SHP‐1‐STAT3‐survivin and Sp1‐p21 cascades are involved in WMJ‐8‐B‐induced MDA‐MB‐231 breast cancer cell death. These results also indicate the potential of WMJ‐8‐B as a lead compound for treatment of breast cancer and warrant its clinical development.